Citizen Manufacturing: Unlocking a New Era of Digital Innovation - Hodges, Steve; Fraser, Mike (IEEE Pervasive Computing, 2022)
We have all come to expect—if not depend upon—the steady march of technology. All manner of pervasive computing devices, applications, and services increasingly support us at home and work. Thankfully, for those tasked with creating future generations of innovative digital technologies, the design and prototyping process continues to get easier. But for hardware, the transition from device prototype to production presents a bottleneck that is restricting the rate and nature of innovation. Imagine instead a world of citizen manufacturing, where individuals are empowered to turn their ideas not only into working prototypes, but also to evolve them organically and seamlessly into viable products. Such an approach could increase consumer choice, grow local and national economies, and facilitate more socially conscious production. We call on the community to join us in pursuit of this goal! We believe that overcoming the many challenges of transitioning from device prototyping to production will unlock a new era of digital innovation that allows more people to explore and benefit from pervasive computing.